ALGORITHM OF DIAGNOSTICS AND TREATMENT OF JUVENILE ARTHRITIS - E.I. Alexeeva; T.М. Bzarova ("Paediatrician" Publishers LLC, 2010)
The theme of the article is one of the most wide-spread rheumatologic diseases - juvenile arthritis (JA). It highlights main questions on epidemiology, classification, pathogenesis of the disease. Authors describe clinical symptoms of different types of JA, diagnostics and differential diagnosis. There is a part of an article with information on drugs used in patients with JA and the algorithm of differentiated treatment of a disease is presented. Authors paid special attention to approaches to biological therapy, conditions for the treatment and management of patients treated with genetically engineered biological drugs. Key words: children, juvenile rheumatoid arthritis, juvenile arthritis, treatment, infliximab, adalimumab, etanercept, rituximab, abatacept, tocilizumab. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(6):78-104)